Mango malformation: Histopathological and histochemical studies on shoot and floral apices - K.S. RAO, A.C.M. KOTI BABU and (Indian Phytopathology, 2002)
In India, mango apical and axillary buds developed into reproductive buds in the winter months which gave rise to panicles. In the warmer months the buds developed into vegetative shoots. The pathogenic interaction with some of the floral buds resulted in high incidences of malformation which started early in the floral season and extended up to April and reestablished in November. Fusarium moniliforme [Gibberella fujikuroi] was often associated with the floral and vegetative apices. The site of infection was marked by infusion of phenolic contents and proteins in the cells. Deposition of starch in the pith cells of the shoot was relatively more in the floral season.